Employee assistance Programm als Führungsinstrument: Die Perspektive der Führungskräfte - Kiefer, Stefanie; Turgut, Sarah (Zeitschrift für Arbeitswissenschaft, 2018)
The present study investigates the antecedents of value beliefs about and the intention to use an employee assistance program (EAP). During a training focusing on Healthy Leadership, 57 leaders of customer organizations of a specific EAP provider were surveyed. The results show a positive relationship between value beliefs about an EAP and the intention to use it. Health-oriented leadership behavior as well as knowledge about an EAP were identified as antecedents of value beliefs about an EAP and the intention to use it. Value beliefs about an EAP were also shown to partially mediate the relationship between health-oriented leadership behavior and the intention to use an EAP. Furthermore, knowledge about an EAP was identified as a partial mediator between health-oriented leadership behavior and the value beliefs about an EAP as well as the intention to use it. Moreover, it could be shown that the value beliefs about an EAP and the intention to use it are higher after participation in the training Healthy Leadership than before.Practical Relevance: The present study’s findings yield first information for organizations willing to increase their leaders’ intention to use an EAP; which can be achieved by fostering health-promoting leadership as well as enhancing knowledge about the EAP. Methods such as a training regarding Healthy Leadership as well as a target-group specific communication concept could be used to support leaders in their role being a navigator and proponent. This should include information and material that make it easier for leaders to recommend and use an EAP.
Online publiziert: 29. Dezember 2017
Gesehen am 21.10.2019